DOI: 10.17077/etd.do05uc95
|View full text |Cite
|
Sign up to set email alerts
|

Male Chinese international students' utilization of and barriers to mental health resources

Abstract: The number of Chinese international students obtaining their education at American institutions of higher education has reached a pinnacle, in that more Chinese international students attend American colleges and universities than ever before (Institute of International Education, 2015). Colleges and universities actively recruit Asian international students, especially those from the People's Republic of China. As Chinese international students continue to represent an ever-greater percentage of the student b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 91 publications
(243 reference statements)
0
20
0
Order By: Relevance
“…In several studies, it was found that masculinity or being male could be a barrier to mental health service utilization for many immigrant students, especially Asian students (n = 10). According to Galligan in 2017, norms of masculinity would be influenced by cultural norms and would advocate for the desire to manage oneself such as the desire to be seen as tough or strong, the feeling of not being able to cry and not having to express one’s emotions, and the desire not to be seen as weak [ 86 ]. Thus, the strong adherence to masculinity among men in Asian communities often leads to their reluctance in seeking mental health services when faced with mental health issues [ 49 , 50 , 52 , 56 , 63 , 68 , 74 , 81 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several studies, it was found that masculinity or being male could be a barrier to mental health service utilization for many immigrant students, especially Asian students (n = 10). According to Galligan in 2017, norms of masculinity would be influenced by cultural norms and would advocate for the desire to manage oneself such as the desire to be seen as tough or strong, the feeling of not being able to cry and not having to express one’s emotions, and the desire not to be seen as weak [ 86 ]. Thus, the strong adherence to masculinity among men in Asian communities often leads to their reluctance in seeking mental health services when faced with mental health issues [ 49 , 50 , 52 , 56 , 63 , 68 , 74 , 81 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Galligan in 2017, norms of masculinity would be influenced by cultural norms and would advocate for the desire to manage oneself such as the desire to be seen as tough or strong, the feeling of not being able to cry and not having to express one’s emotions, and the desire not to be seen as weak [ 86 ]. Thus, the strong adherence to masculinity among men in Asian communities often leads to their reluctance in seeking mental health services when faced with mental health issues [ 49 , 50 , 52 , 56 , 63 , 68 , 74 , 81 , 86 ]. For instance, Alajlan’s study revealed that men were more likely to feel stigmatized by counseling and had lower tolerance scores compared to women [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming gender plays an important role in shaping attitudes toward helpseeking (Tedeschi & Willis, 1993), studies examining the effects of gender on helpseeking behaviors among Asian populations have produced mixed results. Even though gender is not a significant predictor of Chinese students' attitudes toward seeking psychological help (e.g., Tang et al, 2012;Zhang & Dixon, 2003), some researchers have argued that gender has a significant effect on students' help-seeking attitudes in general (Leong & Zachar, 1999), particularly for Chinese, Asian, and Asian-American students (e.g., Chang, 2008;Galligan, 2016;Mojaverian et al, 2013;Sheu & Sedlacek, 2004;Tedeschi & Willis, 1993;Yoon & Jepsen, 2008). In studies where gender was identified as an important factor in help-seeking attitudes, the findings consistently revealed women as reporting more favorable attitudes than men.…”
Section: The Impact Of Gendermentioning
confidence: 99%
“…Although seeking help for psychological reasons is highly stigmatised among the Chinese student population, research has highlighted seeking help for academic supports and web-based interventions as alternatives which may make helpseeking more acceptable. Help-seeking for academic reasons is often considered more socially acceptable among this population and promoting the benefits to study is recommended (Galligan, 2016;Tracey et al,1986).…”
Section: Mental Health and Counsellingmentioning
confidence: 99%